2022
DOI: 10.3390/vaccines10101752
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Use before Influenza Vaccination May Lower the Risks of Influenza and Related Complications

Abstract: Older adults are more likely to have influenza and respond less well to the flu vaccine. We conducted this study to investigate whether pre-influenza vaccination metformin use had an effect on influenza and relevant complications in older adults with type 2 diabetes mellitus. Propensity score matching was used to identify 28,169 pairs of metformin users and nonusers from Taiwan’s National Health Insurance Research Database from 1 January 2000 to 31 December 2018. We used Cox proportional hazards models to calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Diaz et al have demonstrated that metformin could induce 5’- adenosine monophosphate-activated protein kinase (AMPK) phosphorylation in B cells, increase the percentages of circulating switched memory B cells, decrease the pro-inflammatory exhausted memory B cells, decrease B cell-intrinsic inflammation, and improve the in vivo and in vitro antibody response to the influenza vaccine [18] . Our recent study also revealed that pre-influenza vaccination metformin use could reduce the risk of influenza infection in older people with type 2 DM [19] . However, the present study showed that the use of metformin 60, 120, or 180 days before COVID-19 vaccination did not reduce the incidence of COVID-19, and we showed similar results among patients with different ages, sex, ethnic groups, and vaccines, with or without diabetic complications, and insulin use or nonuse.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Diaz et al have demonstrated that metformin could induce 5’- adenosine monophosphate-activated protein kinase (AMPK) phosphorylation in B cells, increase the percentages of circulating switched memory B cells, decrease the pro-inflammatory exhausted memory B cells, decrease B cell-intrinsic inflammation, and improve the in vivo and in vitro antibody response to the influenza vaccine [18] . Our recent study also revealed that pre-influenza vaccination metformin use could reduce the risk of influenza infection in older people with type 2 DM [19] . However, the present study showed that the use of metformin 60, 120, or 180 days before COVID-19 vaccination did not reduce the incidence of COVID-19, and we showed similar results among patients with different ages, sex, ethnic groups, and vaccines, with or without diabetic complications, and insulin use or nonuse.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have shown that metformin significantly reduces the risk of cardiovascular diseases, pneumonia, sepsis, herpes zoster, and post-herpetic neuralgia in patients with type 2 diabetes [23] , [13] , [14] , [15] . The pre-influenza vaccination use of metformin significantly lowered the risk of hospitalization for influenza, pneumonia, mechanical ventilation, and mortality compared to metformin nonusers in older patients with type 2 DM [19] . A meta-analysis and systemic review showed that metformin use was associated with a 27% lower risk of hospitalization for COVID-19 than metformin no-use [16] .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Metformin reduced morbidity and mortality in mice infected with DENV and IAV, but not ZIKV ( 168 , 169 ). Diabetic patients on metformin treatment were found to have lower morbidity and mortality upon influenza virus infection ( 170 ) and a trend toward reduced mortality when infected with SARS-CoV-2 ( 171 ). Contrastingly, metformin showed no clinical benefit in nondiabetic COVID-19 patients ( 172 ).…”
Section: Host-targeted Broad-spectrum Antiviral Approachesmentioning
confidence: 99%
“…Retrospective studies suggest metformin can improve vaccine-induced protection in humans as well. Diabetics on metformin prior to flu vaccination had a lower risk of severe flu infection and associated complications compared to diabetics not on metformin ( Yen et al, 2022 ). More specifically, the risk of hospitalization for influenza, pneumonia, cardiovascular disease, invasive mechanical ventilation, death due to cardiovascular diseases, and all-cause mortality in older adults with T2D was decreased after contracting flu when participants were taking metformin prior to vaccination ( Yen et al, 2022 ).…”
Section: Clinical Trials With Metformin and Sars-cov-2 Or Influenza V...mentioning
confidence: 99%